IsiZulu adoptives from english and afrikaans: an optimality theory analysis - Khan, Tasmia (My University, 2016)
The study examines some phonological characteristics of isiZulu adoptives, derived from English and Afrikaans. IsiZulu is a member of the Nguni group of languages, whereas English and Afrikaans are linguistically related, belonging to the Indo-European language group. These languages have different phonological structures and borrow words from each other. This research focuses on the repair strategies employed in isiZulu to adapt and rephonologise English and Afrikaans loanwords. Rephonologisation is a process that alters the structure of a word to conform to the phonological structure of a recipient language. This investigation focuses on the segmental and syllable structure modifications that loanwords undergo in order to make them fit into the preferred phonological structure of isiZulu. Particular repair strategies described and accounted for in this study include, inter alia, segment substitution, vowel epenthesis, glide epenthesis, and segment deletion. Certain isiZulu adoptives are completely rephonologised while others only undergo partial adjustment. This indicates the retention, in certain instances, of English and Afrikaans segmental features and syllable structures within isiZulu loanword phonology. This study examines both variants, the fully and the partially rephonologised adoptives. Additionally, with the objective of contributing to phonological typology, the research evaluates and compares its findings to observations made by prior, similar investigations for chiShona (Kadenge, 2012; Kadenge & Mudzingwa 2012) and isiNdebele (Mahlangu, 2007; Skhosana, 2009). The broader objective of this study is to explore the synchronic phonology of isiZulu, exposing the phonological changes that are taking place in this language due to contact with English and Afrikaans. In addition, a vast corpus of isiZulu loanwords (data) from English and Afrikaans is presented; contributing a foundation for utilisation in future studies. The overall analysis of the data is couched within Optimality Theory (OT: Prince & Smolensky 2004), which emphasises that surface forms of language reflect the resolution of conflicts between constraints (Kager, 1999). The intra-linguistic variations of loanwords are explained in terms of constraint re-ranking, which is responsible for the phonological shape of loanwords in isiZulu and is addressed herein.
A thesis submitted to the University of the Witwatersrand in fulfilment of the requirements of the degree of Master of Arts in Linguistics. 11 March 2016
Keywords: Zulu language--Grammar; Zulu language|xPhonology.